Müzik Eğitiminde İşbirlikli Öğrenme Yönteminin Kullanımının İncelenmesi - HALVAŞİ, BÜLENT (My University, 2022)
The aim of this research is to present the thesis, article, symposium statement and book chapter researches studied in the discipline of music education in Turkey by using the cooperative learning method, and to analyze these researches in terms of publication year, publication type, method, cooperative learning technique, sampling group, and examine the results obtained comprehensively. The study carried out using the general survey model in Turkey and whose full text was reached were taken into consideration in this analysis. In the research, document analysis technique was used as a data collection tool. The data obtained were analyzed with a descriptive analysis approach and evaluations were made for the utilization of cooperative learning method in the field of music education. As a result of the research, it has been presented that a total of 23 researches were conducted, the first of which was in 1995, using the cooperative learning method in music education in Turkey and the most studies were carried out in the type of articles. It has been observed that studies were mostly designed according to the experimental model, more than half of the studies were performed at the undergraduate level with respect to applied teaching level, using primarily Jigsaw and Co-Learning cooperative learning techniques. In the studies carried out using the cooperative learning method in music education, it has been concluded that the cooperative learning method has the most positive effects on the students' acquisition of social skills. Working together (positive addiction) for group success is the most common social skill in the researches. As a result of the research, it has been concluded that the cooperative learning method in music education has positive effects on students' performance, academic achievement, attitudes towards the lesson and music. Structured Abstract: Introduction: The utilization of cooperative learning methods together with active learning methods in educational environments and scientific studies are increasing worldwide. The fact that the cooperative learning model is a model that can be successfully applied in different age groups, different grade levels, different courses and teaching subject areas makes it more used than other active learning methods. The researches using the cooperative learning method reveals that this method provides many benefits to students academically, socially and psychologically compared to traditional methods. When the relevant literature is examined, it is seen that although there have been many studies on cooperative learning in different disciplines in our country since the 1990s, the number of studies using the cooperative learning method in the field of music education is limited. The aim of this research is to present the thesis, article, symposium statement and book chapter researches studied in the discipline of music education in Turkey by using the cooperative learning method, and to analyze these researches in terms of publication year, publication type, method, cooperative learning technique, sampling group, and examine the results obtained comprehensively. Theoretical Framework: Cooperative learning is a learning process where students help each other learn in an academic subject by being divided into heterogeneous and mixed groups of 2-6 students in order to achieve a common goal, group success is rewarded in different ways, students develop positive addictive on their groupmates through group work, communication and social skills are improved (Slavin, 1995; Watson, 1992; Açıkgöz, 1992; Gömleksiz, 1993; Doymuş vd., 2005). The first study on cooperative learning in Turkey was conducted by Açıkgöz in 1987, “Collaboration? Contest?” is research. Subsequently, the research conducted and published by Açıkgöz in the 1990’s enabled the cooperative learning method to be recognized in our country and allowed researchers from different disciplines to conduct researches in this field (Açıkgöz, 1992, p. 151). Method: In this study, the general survey model, which is one of the survey model types, was used in order to examine how and at what level the cooperative learning method is used in terms of various variables in the music education. The general survey model is the survey studies that carried out on the whole population or a sampling group in order to reach a general judgment about the universe in a universe consisting of many elements (Karasar, 2016; p.111). In the research, document analysis technique was used as a data collection tool. Document analysis is a data collection process, also known as documentary scanning, that includes the processes of finding, examining, taking notes and evaluating relevant sources for a specific purpose. The data obtained were analyzed with a descriptive analysis approach and evaluations were made for the use of cooperative learning method in the music education. In this study, criterion sample method was used to determine the sampling group. Criterion sampling is a sampling method in which observation units can consist of people, objects, events or situations with certain qualifications and criteria and units that meet the criteria determined for the sample group are taken into the sample group (Büyüköztürk vd., 2016; p. 92). The sample of this research consists of 23 studies in total, including domestic studies in Turkey. Findings: In Turkey, the first research carried out using the cooperative learning method in the music education is a doctoral thesis conducted in 1995. It is observed that between the years 1991-2000, 5 studies were carried out using the cooperative learning method in the music education, 3 studies were carried out between 2001-2010, 15 studies were carried out between 2011-2020 and a total of 23 researches were carried out. There was no study in 2021 and 2022. Researchers have conducted studies in the highest number (10) of thesis types. It is seen that 14 of the 23 studies conducted using the cooperative learning method in the music education were carried out using the experimental design with pretest-posttest control group. In addition, all 5 doctoral theses were designed according to the experimental model. In the studies, in terms of cooperative learning techniques, Jigsaw-I and Co-Learning techniques were used with a maximum of 7 studies. The student teams achievement divisions (STAD) technique was used in 5 studies. When the sampling group in which the studies carried out using the cooperative learning method in the field of music education are examined, it is seen that 12 studies are at the undergraduate level, 6 studies are at the secondary school level, 5 studies were applied to students at primary education level. It is noteworthy that no research has been conducted on high school students. When the results of the research conducted in the field of music education using the cooperative learning method were examined, it was concluded that the cooperative learning method was the most effective in terms of gaining social skills on the study groups. Working together (positive addictive) for group success is the most common social skill in researches. In terms of musical performance, 11 studies revealed that cooperative learning was effective on performance, while in two study there wasn’t difference between the experimental and control group. According to the results of the research, it was concluded that the cooperative learning method was effective on the academic achievement of the study groups in 6 studies and on the attitudes of the study groups in 10 studies. When the attitude theme was examined, it was concluded that positive attitude towards the lesson was observed in 5 studies, positive attitude towards music was observed in 3 studies, and there was no difference between the experimental group and the control group in attitude towards the lesson in 1 study. Results: As a result of the research, it has been presented that a total of 23 researches were conducted, the first of which was in 1995, using the cooperative learning method in music education in Turkey and the most studies were carried out in the type of articles. It has been observed that studies were mostly designed according to the experimental model, more than half of the studies were performed at the undergraduate level with respect to applied teaching level, using primarily Jigsaw and Co-Learning cooperative learning techniques. In the studies carried out using the cooperative learning method in music education, it has been concluded that the cooperative learning method has positive effects on the students' acquisition of social skills, musical performance, academic success, attitudes towards the lesson and music. Keywords: Music education, Constructivism, Active learning, Cooperative learning, Co-Learning

Bu araştırmanın amacı, ülkemizde müzik eğitimi alanında işbirlikli öğrenme yöntemi kullanılarak yapılan tez, makale, sempozyum bildirisi ve kitap bölümü niteliğindeki araştırmaları ortaya koyarak, bu araştırmaları yayın yılı ve yayın türü, yöntemi, kullanılan işbirlikli öğrenme tekniği, uygulandığı öğrenim kademesi ile elde edilen sonuçlar bakımından kapsamlı bir şekilde incelemektir. Genel tarama modeli kullanılarak yürütülen bu araştırmada, yurtiçinde gerçekleştirilen ve belirlenen kriterleri sağlayan araştırmalar çalışma kapsamına alınmıştır. Araştırmada, veri toplama aracı olarak doküman analizi tekniği kullanılmıştır. Elde edilen veriler, betimsel analiz yaklaşımıyla incelenerek müzik eğitimi alanında işbirlikli öğrenme yönteminin kullanımına yönelik değerlendirmeler yapılmıştır. Araştırma sonucunda, ülkemizde, müzik eğitiminde işbirlikli öğrenme yöntemi kullanılarak ilk olarak 1995 yılında olmak üzere toplam 23 araştırma yapıldığı, en çok makale türünde çalışmalar gerçekleştirildiği ortaya konulmuştur. Bu araştırmaların, çoğunlukla deneysel modele göre tasarlandığı, uygulanan öğretim kademesine göre yarıdan fazlasının lisans düzeyinde uygulandığı, en fazla Birleştirme-I (Jigsaw) ve Birlikte Öğrenme işbirlikli öğrenme tekniklerinin kullanıldığı gözlenmiştir. Müzik eğitiminde işbirlikli öğrenme yöntemi kullanılarak gerçekleştirilen araştırmalarda, işbirlikli öğrenme yönteminin öğrencilerin en çok sosyal beceriler kazanma üzerinde olumlu etkileri olduğu sonucuna ulaşılmıştır. Grup başarısı için birlikte çalışma (olumlu bağımlılık) kazanımı, araştırmalarda en fazla elde edilen sosyal beceridir. Araştırma sonucunda, müzik eğitiminde işbirlikli öğrenme yönteminin öğrencilerin performans, akademik başarı, derse ve müziğe yönelik tutumları üzerinde olumlu etkileri olduğu sonucuna ulaşılmıştır. Anahtar Kelimeler: Müzik eğitimi, Yapılandırmacılık, Aktif öğrenme, İşbirlikli öğrenme, Birlikte öğrenme
The Utilization Analysis Of Cooperative Learning Method in Music Education
Keywords: Müzik eğitimi; Yapılandırmacılık; Aktif öğrenme; İşbirlikli öğrenme; Birlikte öğrenme; Music education; Constructivism; Active learning; Cooperative learning; Co-Learning